Determination of active travel speed for minimum air pollution inhalation. Issue 3 (16th March 2017) - Bigazzi, Alexander Y.
ABSTRACT: A higher active travel speed has offsetting impacts on air pollution inhalation dose through higher breathing rate but shorter exposure duration. The net effect of speed choice on inhalation dose for pedestrians and bicyclists has not been established. This paper derives equations for pedestrian and bicycle steady-state minimum-dose speed (MDS). Parameter distributions from the literature are applied to a synthetic population of travelers to calculate individual MDS. Results strongly support the existence of a definable MDS, which is near observed travel speeds for urban pedestrians and bicyclists. For a wide range of travelers, the MDS is 2–6 km/h while walking and 12–20 km/h while bicycling, decreasing with road grade at a rate similar to observed speeds. On level ground, pedestrian and bicycle MDS corresponds to a moderate-intensity physical activity level (3–6 MET). Small deviations from the MDS have little effect, but large deviations (by more than 10 km/h for bicycling) can more than double inhalation dose over a fixed distance. It appears that pedestrians and bicyclists choose travel speeds that approximately minimize pollution inhalation dose, although pollution is unlikely a primary motivation.